Negara Indonesia Persfektif Islam: Sebagai Bentuk Penguatan Wawasan Kebangsaan - Hosaini; Muhammad Ihyaul Fikro (Moderasi : Journal of Islamic Studies, 2021)
The ‘Orde Baru’ fell from power, the idea of ​​establishing an "Islamic state" reappeared. This makes a lot of disturbing many circles of society, including the Muslim population. This research is a literature review. The role of pesantren and Muslims is quite large in building the spirit of nationalism in seizing independence and Nahdlatul Ulama (NU) as the largest socio-religious organization in Indonesia led by traditional pesantren kiai - has offered a brilliant theological solution through political fiqh in the relationship between Islam and Pancasila.